Bladder dysfunction and quality of life for people with multiple sclerosis. (4th December 2015) - Browne, Catherine; Salmon, Nancy; Kehoe, Maria
Abstract: Purpose : Bladder dysfunction affects 75% of people with multiple sclerosis (MS). People with MS are reluctant to seek treatment for this distressing symptom. This is the first-known study to explore in depth how bladder dysfunction interferes with quality of life for people with MS. Methods : Nineteen individual semi-structured interviews were conducted (M = 8, F = 11). Participants had a definite diagnosis of MS, aged between 37 and 64 years and had at least one bladder dysfunction symptom. The audio-recorded interviews lasted up to 90 min and were transcribed verbatim. Results : Thematic analysis within NVivo10 yielded two key themes: (1) Disruptions and loss and (2) ways of knowing. "Disruptions and Loss" explores how bladder dysfunction interrupted daily living activities and how this contributed to experiencing loss. "Ways of knowing" portrays the types of knowledge that existed around bladder dysfunction. Participants described using their experiential knowledge to self-manage bladder symptoms without advice from healthcare providers. Conclusions : Bladder dysfunction imposes major disruptions on daily life. People with MS attempt to self-manage their bladder symptoms, despite current barriers to navigating existing healthcare infrastructure. Understanding these barriers and the individual strategies employed by people with MS are the first steps in facilitating independent management of bladder dysfunction. Implications for Rehabilitation: Each individual's experience of bladder dysfunction is unique. Healthcare professionals must be prepared to discuss all disruptions and losses associated with bladder dysfunction for people with MS. People with MS have a vast range of knowledge in relation to their own bladder symptoms and healthcare professionals need to explore their existing self-management strategies during assessment. People with MS and healthcare professionals need to be educated on the wider health implications relating to bladder dysfunction.